Analisis visi dan misi Koperasi Syariah di Indonesia berdasarkan prinsip Islam: Bahasa indonesia - Fauzan, Iqbal Zul (Maliki Interdisciplinary Journal, 2023)
Strategic management is an analysis of a company’s strategy to have clear objectives. Strategic management has stages in analyzing a company, one of which is analyzing the company’s vision and mission. This research takes the subject Koperasi Produsen Agro Niaga Jabung Syariah " and " Koperasi Benteng Mikro Indonesia ". The aim of the research is to compare and analyze the two sharia cooperatives. The data used to analyze the two cooperatives uses descriptive data. The analysis used by each cooperative is the same, namely by analyzing their vision and mission and then matching it with sharia principles.